u-kamieno būdvardžių šaknies vokalizmo variantai (variacijos balt. a : e, a : silpnasis laipsnis, a : e : silpnasis laipsnis) - Vanags, Pēteris (Baltistica, 1994)
ROOT VOWEL VARIATIONS IN u-STEM ADJECTIVES (VARIATIONS BALT. a: e, a: ZERO-GRADE, a: e: ZERO-GRADE) Root vowel variation and different variants in Baltic u-stem adjectives (e.g., Lith. dagùs : degùs) have originated as a result of mixing different word-formation patterns owing to the productivity of u-stem adjectives. Baltic a grade is to be considered primary where root vocalism is formed by a single vowel (variation a:e, root pattern -CVC-; e.g., dagùs, lakùs, lapùs, drabùs, srabùs). The same assertion is right for the variation a:e in variants with root pattern -CViC-, -CVRC-(e.g., brandùs, drąsùs, dalsùs, garbùs, dargùs). Zero-grade must have been primary where it is possible (variations a : zero-grade, a : e : zero-grade, root pattern -CViC-, -CVuC-, -CVRC-), yet relatively long ago (at least in East-Baltic) an a grade has become characteristic of this root pattern (e.g., alsùs, rajùs, baugùs, gaudùs, slaidùs).